Fathers’ involvement in handling growth disorder of children family members: a systematic review - Sulistyono, R Endro; Hayati, Nurul; Abdillah, Achlish (Journal of the Pakistan Medical Association, 2023)
Objective: To find out fathers’ involvement in the treatment of growth disorders. Methods: The systematic review comprised search on Scopus, CINAHL, ScienceDirect, SpringerLink, ProQuest and Google Scholar databases for studies published in English language between January 2017 and March 2022 and described fathers’ roles in handling stunting in children. The keywords used along with Boolean operators included father, paternal, involvement, engagement, role, stunting, and growth disorder. The studies shortlisted were subjected to charting and narrative analyses. Results: Of the 699 studies initially found, 13(1.85%) were analysed in detail. Four factors identified were economic support, instrumental support, nurturing the children, and health risk behaviour. Strategies to increase fathers’ involvement related to internal and external barriers. Conclusion: Fathers’ role is crucial in handling growth disorder in children. Growth disorder management strategies need to involve fathers and mothers by considering the identified barriers and potential facilitators. Keywords: Child, Mothers, Gender, Health risk, Nutrition.